The Biology of Aging and Cancer: Frailty, Inflammation, and Immunity. Issue 4 (July 2017) - Zhang, Xinwen; Meng, Xin; Chen, Yiyin; Leng, Sean X.; Zhang, Haiyan
Abstract : Abstract: The majority of patients with common malignancies are older adults. Intrinsic complex biological changes of aging along with inflammation, immunosenescence, age-associated chronic diseases, and extrinsic environmental and psychosocial factors have significant impact on not only development and behavior of individual malignancies, but also physiologic reserve and vulnerability of older patients who suffer from them. As a result, clinical practice of geriatric oncology demands integration of careful geriatric assessment and management. This article provides an overview of basic biology of aging and its relationship with cancer. After a brief introduction about the definition and mechanisms of aging, as well as age-related biological and physiological changes, the discussion mainly focuses on recent development and insights into the relationship of frailty, inflammation, and immunity with cancer, highlighting how the new knowledge can help further improve assessment and treatment of older patients with malignancies and promote cancer research.